Pemrosesan Sinyal Data Sub-bottom Profiler Substrat Dasar Perairan Selat Lembeh - Steven Solikin; Henry M. Manik; Sri Pujiyati; Susilohadi Susilohadi (Jurnal Rekayasa Elektrika, 2017)
An accurate mapping of ocean seabed is needed to answer the challenges faced by the marine scientist today. Sub-bottom profiler present as one of the acoustics system which used to describe the sediment layer profile of the ocean bottom, as well as the thickness of the layer and the stratigraphy. The purpose of this research is to describe the 2D profile and to determine the value of the reflection coefficient of the sediment layers in Lembeh Strait, North Sulawesi. The reflection coefficient is necessary to be analyzed related to the seabed sediment grain size and type. The data acquisition carried out using Syqwest Stratabox sub-bottom profiler with the frequency of 10 kHz. FFT signal processing and bandpass filter are applied to relieve noise from main signals as well as to get better results. The results of data processing show that seafloor sediments have a value of the surface reflection coefficients which ranged between 0.1168 until 0.7938 with type iron smooth sand.